Never Let a Crisis Go to Waste: Opportunities to Reduce Social Disadvantage from COVID‐19. (30th June 2021) - Baxter, Janeen; Cobb‐Clark, Deborah; Cornish, Alexander; Ho, Tiffany; Kalb, Guyonne; Mazerolle, Lorraine; Parsell, Cameron; Pawson, Hal; Thorpe, Karen; De Silva, Lihini; Zubrick, Stephen R.
Abstract: This article identifies and examines a range of policy reform opportunities in Australia arising from COVID‐19. The authors demonstrate how COVID‐19 presents unique opportunities for rethinking and redesigning long‐standing rules and regulations covering how people live and work in Australia, with some opportunities arising coincidentally and others requiring purposeful policy and institutional redesign. They present a broad range of ideas to address entrenched disadvantage in health, labour markets, the tax and transfer system, gender equality, education, housing and criminal justice in Australia, in order to leverage the COVID‐19 crisis to build a better society .